Epithelial cells bearing class II molecules stimulate allogeneic human colonic intraepithelial lymphocytes. Issue 8 (August 1992) - Hoang, P; Crotty, B; Dalton, H R; Jewell, D P
Abstract : HLA-DR+ gut epithelial cells may present antigen to intraepithelial lymphocytes (IEL). This study aimed to isolate an IEL population from the human colon to activate CD3 + IEL by a human colonic epithelial cell line (HT-29), bearing different concentrations of class II antigen (HLA-DR). IEL were isolated by a mechanical method from six patients with ulcerative colitis (UC) and from 14 control patients. IEL were cocultured with HT-29 which had been induced to express class II molecules by gamma-interferon (IFN-gamma) in a dose dependent manner. The phenotype and the subsequent expression of activation markers by the IEL were determined to two colour flow cytometry. The IEL population had a CD4/CD8 ratio similar to that seen in tissue sections. In the mixed cell culture, the degree of IEL activation showed a positive correlation with the degree of HLA-DR expression by the HT29 cells and the IEL secreted a IFN-gamma like factor that in turn stimulated the HT-29. Thus, depending on their expression of HLA molecules, colonic epithelial cells are able to activate CD3+CD8+IEL.